Awareness of physical activity promotion, physical activity, and sedentary behavior in elderly Japanese - Takayuki Tajima; Yoshinobu Saito; Riri Kato; Yayoi Kibayashi; Motohiko Miyachi; I-Min Lee; Yuko Oguma (Japanese Society of Physical Fitness and Sports Medicine, 2018)
This study describes relationships between awareness of physical activity (PA) promotion and duration of PA and sedentary behavior (SB) in elderly Japanese. Following a community-wide intervention, 874 individuals 65 years or over were selected via population-based random sampling of 3,000 adults aged 20 years or over living in Fujisawa City, and asked to complete self-administered questionnaires; 550 responded and 373 with data on pertinent variables were included. Forty-eight percent (179/373) stated that they recognized elements of the Japanese PA guidelines such as the "Active Guide" and "+10 (plus ten)." The median duration of PA, of intensity at least equal to walking, and SB among all participants were 100 minutes/day and 300 minutes/day, respectively. Duration of PA did not significantly differ by promotion awareness (Odds Ratio (OR) for ≥100 minutes/day among those aware = 1.02, 95% Confidence Interval (CI) = 0.65-1.62); however, duration of SB did (OR for <300 minutes/day = 1.60, 95% CI = 1.01-2.53). Awareness of PA promotion in elderly Japanese is related to decreased SB, but not increased PA of intensity at least equal to walking.